Suleiman Al-Nabulsi and His Position on Arab Nationalist Causes - Al Shyyab, Ibrahim Ahmad; Al-Bashayreh , Ali Ibrahim; Amayreh , Mohammed Salem; Omari , Omar Saleh Al; Al-jabali , Khaled Hassan (Journal of Ecohumanism, 2024)
This study addressed the position of Suleiman Al-Nabulsi on many Arab and national causes, as Al-Nabulsi is considered one of the men of Jordan had a prominent role in the Jordanian and Arab political life. His life reflected to a large extent the reality of political life and its interactions in the Jordanian arena and the Arab world at large ,this study aims to underline Al-Nabulsi ’s position regarding all causes at Jordanian and Arab national levels , such as the Palestinian situation, Arab unity, the Algerian revolution, the Baghdad Pact, the tripartite aggression against Egypt and other Jordanian and national causes, in addition to clarifying Al-Nabulsi ’s philosophy of national loyalty, which stems from principle of Arab existence unity. he is one of the prime ministers in Jordan who did not limit nationalism just at Jordan’s level , besides his role in the social reform that aims to attain more of democracy and opposition to foreign mandates which he considered as a form of colonialism (Al-Mousa, 1986, p. 57), and therefore it was natural that this philosophy will be in conflict with the philosophy of the state which aims to maintain its entity and independence ,the descriptive historical method was used that relies on the historical events as they appeared in their sources ,and to apply critical approach and analyze them in a scientific ,rational and neutral objectivity far from prejudice .the study reached many conclusions some of which are :the national philosophy of Al-Nabulsi that transcends the political and geographical boundaries of Jordan ,because he upholds the high values and ideals in his calculations ,and in fact he tried to subject reality to those values , also President Nasser’s ideas regarding unity has a great impact on his personality ,so he experienced a conflict between the loyalty to the country ,and the loyalty to Arab nationalism by president Nasser ,so naturally he saw no conflict between the two loyalties to the country on the one hand and the larger Arab nationalism on the other hand (Al-Mousa 1986 ,P 58 ), but the two loyalties complimented each other and he defended this concept until the last day of his life.